Computational study on various properties of CaO-Al2O3-SiO2 mold flux. Issue 6 (15th April 2019) - Yu, Zhi-Gang; Leng, Hai-Yan; Wang, Li-Jun; Chou, Kuo-Chih
Abstract: Mold fluxes play a crucial role for the control and optimization of the continuous casting of steel. The CaO-Al2 O3 -SiO2 system is gradually replacing the traditional CaF2 -based slags to fight against fluoride pollution. Comprehensive physicochemical properties of mold fluxes, such as viscosity, electrical conductivity and sulfide capacities, are all critical to the quality of the products. A phenomenological model has been used to calculate all these comprehensive physicochemical properties of CaO-Al2 O3 -SiO2 mold flux. Satisfactory agreements between the experimental data and the predicted results of viscosity, electrical conductivity and sulfide capacities for CaO-Al2 O3 -SiO2 system are observed. To have a more reliable evaluation of the present model, the calculated results by some empirical models are also carried out for comparation. It is anticipated that this new model will play more and more important role in estimating the physicochemical property of mold fluxes.